Basnie, opowiesci, gadki - Kolberg, Oskar, 1814-1890.; Lezenska, Katarzyna; Sedziwy, Anna. (Warszawa : Proszynski i S-ka, 1998)
Tales and stories collected by Oskar Kolberg, who was a noted Polish folklorist. Ages 7-12.